Pressure abnormalities in patients with Zenker's diverticulum using pharyngeal high‐resolution manometry - Rosen, Sarah P. (Laryngoscope Investig Otolaryngol, 2020)
OBJECTIVES: Zenker's diverticulum is associated with reduced cricopharyngeal compliance and abnormal intrabolus pressure. However, it is unclear how the pharynx compensates for these deficits. Developments in manometric technology have improved our ability to capture pharyngeal pressure events. This study aims to describe the pharyngeal‐upper esophageal sphincter (UES) pressure profile during swallowing in patients with Zenker's diverticulum. METHODS: High‐resolution manometry was performed on 11 patients with symptomatic Zenker's diverticulum and 11 age‐ and sex‐matched healthy controls during 10 mL liquid swallowing tasks. Pharyngeal and UES pressure magnitudes, durations, and integrals were compared between patients and controls using independent t tests. Other manometric parameters, including residual UES pressure at the time of maximum tongue base pressure and pharyngeal‐UES pressure gradient, were also evaluated. A case example using three‐dimensional high‐resolution manometry is presented. RESULTS: Compared with healthy controls, patients with Zenker's diverticulum exhibited pressure abnormalities in the UES region. While baseline and pre‐opening maximum pressures were not different, residual pressures were elevated (P = .001). Pharyngeal‐UES pressure gradients did not differ between the two groups. CONCLUSION: This study used high‐resolution manometry to characterize pharyngeal pressure dynamics in patients with Zenker's diverticulum. The changes occurring at the cricopharyngeus appear to result in persistent UES pressurization during UES opening, rather than high tonic resting pressure. Pharyngeal‐UES pressure gradients, critical to bolus passage, were also preserved in this patient population. LEVEL OF EVIDENCE: 3b.